UNCOVERING KHALED HOSSEINI’S STRUCTURAL FORMULA IN PORTRAYING CONFLICTS ACROSS THREE NOVELS - Wati, Yuni Hera Kusnia (UIN Raden Mas Said Surakarta, 2025)
This research aims to identify the types of conflict and the formula Khaled Hosseini uses to present them. The study uses Folarin’s theory of conflict and Cawelti’s theory of formula as the main frameworks.The data consist of words and sentences that show nine types of conflict according to Folarin’s theory, taken from Hosseini’s three novels: The Kite Runner, A Thousand Splendid Suns, and And the Mountains Echoed. The analysis uses Spradley’s componential analysis method and a structuralist approach to explore how the intrinsic elements in the novels connect to form Hosseini’s formula. The results show six types of conflict: man vs. self, man vs. man, man vs. society, man vs. nature, inter-group conflict, and intra-state conflict. Among these, man vs. society is the most dominant in the first two novels, showing that Hosseini uses a familiar and recognizable pattern of conflict and plot. Meanwhile, in And the Mountains Echoed, he introduces an inventive formula with a plot twist to make the story feel new. Overall, Hosseini’s formula in his novels combines both convention and invention.